2019
DOI: 10.1074/jbc.ra118.006196
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic insights into the role of the reductant in H2O2-driven degradation of chitin by a bacterial lytic polysaccharide monooxygenase

Abstract: 2 The abbreviations used are: LPMO, lytic polysaccharide monooxygenase; AscA, ascorbic acid; GA, gallic acid; CNW, chitin nanowhisker; MHQ, methyl hydroquinone, NaAc, sodium acetate; NAG eq , N-acetylglucosamine equiv-alents; SmLPMO10A, chitin active lytic polysaccharide monooxygenase from Serratia marcescens; R, reductant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 64 publications
(110 reference statements)
9
89
0
Order By: Relevance
“…First, we observed that the rate of NcLPMO9C increased linearly with the concentration of ascorbate. While we cannot exclude experimentally that the assays may not have been carried out under saturating ascorbate concentrations, a recent study showed that the bacterial LPMO10A from Serratia marcescens had an apparent K M -value of 2 µM for ascorbate [44]. Even if the K M -value of NcLPMO9C for ascorbate would be 50-times higher, the high 0.5-6 mM ascorbate concentration present in our assays should still provide sufficiently saturating conditions to achieve maximal turnover.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…First, we observed that the rate of NcLPMO9C increased linearly with the concentration of ascorbate. While we cannot exclude experimentally that the assays may not have been carried out under saturating ascorbate concentrations, a recent study showed that the bacterial LPMO10A from Serratia marcescens had an apparent K M -value of 2 µM for ascorbate [44]. Even if the K M -value of NcLPMO9C for ascorbate would be 50-times higher, the high 0.5-6 mM ascorbate concentration present in our assays should still provide sufficiently saturating conditions to achieve maximal turnover.…”
Section: Discussionmentioning
confidence: 90%
“…A growing body of evidence demonstrates that LPMOs use H 2 O 2 as cosubstrate with a much higher catalytic efficiency than O 2 [26,28,44,51]. While the cosubstrate preference of LPMOs in their native environments is still debated [29] the efficient peroxygenase reactivity may be beneficial in industrial settings to achieve faster biomass depolymerization [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For their catalytic cycle, LPMOs require an external reductant 16 and one of two cosubstrates, molecular oxygen (O 2 ) or hydrogen peroxide (H 2 O 2 ) 17 . The cosubstrates interact with a reduced copper active site forming a reactive intermediate which can then oxidize the substrate.…”
Section: Introductionmentioning
confidence: 99%